RHETORICAL ANALYSIS ON THE SPEECH â€œWE SHALL FIGHT ON THE BEACHESâ€ BY WINSTON CHURCHILL - Wardhana, I Gede Neil Prajamukti; Christian, Igo Bani; Dewi, Ni Luh Desy Suari; Utami, Gek Wulan Novi (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTSpeech and the art of persuasion are powerful tools if delivered and done in the correct orders. Acrucial moment can be created with such words and little action, speeches inspire people to domore and become more than themselves. The art of persuasion or rhetoric is a detrimental tool thatcan be sharper than a sword; a set of correctly used words with the right tone can be devastating.This paper and the author aim to analyze the rhetorical devices that were used in WinstonChurchill's speech on the Second World War â€œWe Shall Fight on the Beachâ€, using the three mainpillars that Aristotle pioneered in the rhetorical device of the art of persuasion. The method of thestudy is by reading the speech text and analyzing it thoughtfully. The analysis also examinesdescriptive vocabulary and observe the ability of the speaker to adjust their words to inflict aneffect on society (Van Herk, 2015). This study found 3 parts they are Logos, Pathos, and Ethos asthe main of rhetorical language.Keywords: rhetoric, rhetorical language, speechesABSTRAKPidato dan seni persuasi adalah alat yang ampuh jika disampaikan dan dilakukan dengan urutanyang benar. Momen penting dapat diciptakan dengan kata-kata dan tindakan kecil seperti itu,pidato menginspirasi orang untuk berbuat lebih banyak dan menjadi lebih dari diri merekasendiri. Seni persuasi atau retorika adalah alat merugikan yang bisa lebih tajam dari pedang;satu set kata yang digunakan dengan benar dengan nada yang tepat dapat menghancurkan.Tulisan ini dan penulis bertujuan untuk menganalisis perangkat retorika yang digunakan dalampidato Winston Churchill tentang perang dunia kedua â€œWe Shall Fight on the Beachâ€, denganmenggunakan tiga pilar utama yang dipelopori Aristoteles dalam perangkat retorika senipersuasi. Metode penelitiannya adalah dengan membaca teks pidato dan menganalisisnya secararenungan. Analisis ini juga menguji kosakata deskriptif dan mengamati kemampuan pembicarauntuk menyesuaikan kata-kata mereka untuk menimbulkan efek pada masyarakat (Van Herk,2015). Penelitian ini menemukan 3 bagian yaitu Logos, Pathos, dan Ethos sebagai bahasa retorikautama.Kata kunci: retorika, bahasa retorika, pidato